ION OF CHIOS: THE CASE OF A FOREIGN POET IN CLASSICAL SPARTA. (21st February 2019) - Stewart, Edmund
Abstract : χαιρέτω ἡμέτερος βασιλεὺς σωτήρ τε πατήρ τε· ἡμῖν δὲ κρητῆρ' οἰνοχόοι θέραπες κιρνάντων προχύταισιν ἐν ἀργυρέοις· †ὁ δὲ χρυσὸς οἶνον ἔχων χειρῶν νιζέτω εἰς ἔδαφος.† σπένδοντες δ' ἁγνῶς Ἡρακλεῖ τ' Ἀλκμήνηι τε, Προκλεῖ Περσείδαις τ' ἐκ Διὸς ἀρχόμενοι πίνωμεν, παίζωμεν· ἴτω διὰ νυκτὸς ἀοιδή, ὀρχείσθω τις· ἑκὼν δ' ἄρχε φιλοφροσύνης. ὅντινα δ' εὐειδὴς μίμνει θήλεια πάρευνος, κεῖνος τῶν ἄλλων κυδρότερον πίεται. May our king rejoice, our saviour and father; let the attendant cup-bearers mix for us a crater from silver urns; †Let the golden one with wine in his hands wash to the base† Pouring libations piously to Heracles and Alcmene, Procles and the sons of Perseus and Zeus first of all, let us drink, let us play, let our song rise through the night. Dance someone, willingly begin the festivities. And anyone who has a fair girl waiting to share his bed will drink more like a man than all the others. (Ion, fr. 27 West = fr. 90 Leurini)